2021
DOI: 10.3892/etm.2021.9874
|View full text |Cite
|
Sign up to set email alerts
|

Serum NT‑proBNP and TUG1 as novel biomarkers for elderly hypertensive patients with heart failure with preserved ejection fraction

Abstract: Patients with heart failure with preserved ejection fraction (HFPEF) account for ~50% of all cases of heart failure and their clinical prognosis is poor. The present study attempted to investigate the diagnostic value of circulating long non-coding RNA taurine upregulated gene 1 (TUG1) for HFPEF in subjects with hypertension. Between January 2017 and January 2019, 80 aged/elderly hypertensive patients with or without HFPEF were recruited for the present study. The concentration of N-terminal pro-brain natriure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The included studies were published between 2007 and 2021. Twenty-three studies were conducted in China [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; ten in the United States [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; five in Iran [ 47 , 48 , 49 , 50 , 51 ]; four in Italy [ 52 , 53 , 54 , 55 ]; three in the Netherlands [ 56 , 57 , 58 ]; three in Germany [ 59 , 60 , 61 ]; two in Taiwan [ 62 , 63 ]; two in Australia [ 64 , 65 ]; and one each in New Zealand [ 66 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were published between 2007 and 2021. Twenty-three studies were conducted in China [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; ten in the United States [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; five in Iran [ 47 , 48 , 49 , 50 , 51 ]; four in Italy [ 52 , 53 , 54 , 55 ]; three in the Netherlands [ 56 , 57 , 58 ]; three in Germany [ 59 , 60 , 61 ]; two in Taiwan [ 62 , 63 ]; two in Australia [ 64 , 65 ]; and one each in New Zealand [ 66 …”
Section: Resultsmentioning
confidence: 99%
“…Nine of the included studies reported the regulation of lncRNA in HF patients [ 23 , 29 , 31 , 34 , 36 , 41 , 53 , 54 , 59 ]. Four studies involved the examination of lncRNA in cardiac tissue, one study in EAT and one in PBMCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 , 5 HF refers to clinical syndromes characterized by pulmonary and/or body circulation stasis. Because of its high morbidity and mortality, 6 , 7 HF has become a significant contributor to mortality worldwide and a pressing health concern. 8 As a result, early prevention and diagnosis of HF are critical for mitigating relevant symptoms and improving the prognosis of these patients.…”
Section: Introductionmentioning
confidence: 99%